Sīrat al-Shā‘ir Akram al-Za‘bī wa Hayātuh al-‘Ilmīyah wa Marja‘īyātuh al-Thaqāfīyah - Ferial Musa Abdullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study offers a comprehensive analysis of the role of nature in the poetry of contemporary Jordanian poet Akram Al-Zoubi. It begins with an overview of his biography, then explores the concept of nature poetry, its evolution through various literary periods, and an analysis of selected poems. The research distinguishes between two types of nature: silent (trees, mountains, rivers) and vocal (birds, animals). Al-Zoubi masterfully combines these elements to express personal feelings while addressing social and emotional themes. The study emphasizes the significance of poetic imagery and repetition as stylistic devices that enhance meaning and rhythm. It highlights how Al-Zoubi’s rural environment deeply influences his vocabulary and imagery, positioning nature as a central element rather than mere scenery. Ultimately, the research concludes that Al-Zoubi elevates nature to a humanistic and aesthetic level, shaping his artistic and intellectual vision. His poetry reflects a profound connection to his environment and cultural heritage, imbuing nature with emotional and symbolic depth. This positions him among poets who see nature as a vital source of inspiration and cultural identity, enriching his poetic expression with deep emotional resonance and universal appeal.